A new and benign hegemon on the horizon? The Chinese century and growth in the global South - Tam NguyenHuua; Deniz Dilan Karaman Örsal (Kiel Institute for the World Economy (IfW), 2019)
This study investigates the impacts of trade with China on the gross domestic product (GDP) of the global South. While the current literature on the growth impacts of trade (by leading partner countries) often neglects the properties of macro panel data, such as cross-sectional dependence, heterogeneity and structural breaks, our models take these features into account. The empirical results of 22 major developing countries over 2000Q1 to 2016Q4 find positive contributions of imports from China to GDP in our studied sample, although the magnitude of these effects is smaller than that of otheremerging and developing economies (not including China) (EDE) and advanced economies (AdE). The authors also show that, in contrast with considerable impacts of exports to EDE and AdE, exports to China have limited effects on the growth of its partners. However, the recent financial crisis marks a turning point of China's role as a major driver of growth in the South. Namely, while contributions of trade with China in its partners after the global crisis are on the rise, the opposite is true for EDE and AdE.Examining the effects by individual countries, they present that the distance between China and its partners and economic development level of its partners are almost irrelevant to the contributions of imports from China to its partners' growth. They provide some important policy recommendations for the global South from these findings.
Keywords: C23; F43; O4; 330; China; growth; developing and emerging economies; international trade; panel data; econometrics; cross-sectional dependence